Saints & saint makers of New Mexico - Boyd, E. frey50 (Santa Fe, NM Laboratory of Anthropology, 1946)
The primitive art of santo making is described in this publication, the first ever that devotes its major content to the facts surrounding the making of santos, the carved wooden figures and painted panels depicting religious objects. The usual medium of plaster of paris was not available, so the people of Rio Grande country were obliged to make their own using available materials. Santos are being collected by museums, in the US as well as overseas.
Keywords: Religious icons -- New Mexico -- 1750-1850 -- United States - Southwest